Erosive wear performance of API X42 pipeline steel. (February 2016) - Okonkwo, Paul C.; Shakoor, R.A.; Ahmed, Essam; Mohamed, A.M.A.
Abstract: The need to transport petroleum products through pipelines has resulted in the increased erosion of the pipeline materials used in the petroleum industry. In this study, dry erosion test was performed using sand blaster erosion machine to investigate the erosive behavior and mechanism relative to API X42 pipeline steel. Different particle velocities in the range of 20 to 80 m/s were applied at different test durations, while the incident angle was kept constant. The results showed that the plowing mechanism was prevailing at higher velocity and longer test duration. Plastic deformation, embedment of the erodent particle on the target material surface and plowing were observed at lower velocity. Understanding the transition in the erosion mechanism as the particle velocity increases may be a vital importance to the petroleum industry. This will also aid in the erosion models employed for future erosion analysis. Highlights: Erosive mechanism of API X42 pipeline steel was investigated using dry erosion test. Different particle velocities for different test durations were applied. The plowing mechanism was prevailing at higher velocity and longer test duration. Plastic deformation & embedment of solid particles were observed at lower velocity.